Quantitative and Qualitative Analysis of Results in Experimental Research on the Control Stage of Future Educators’ Self-Expression in Culture Development of Artistic Activity - Onyshchuk, Iryna (Pedagogical Discourse, 2019)
The article reflects the results on the control stage of experimental and research work on future pre-school teachers’ self-expression culture development in artistic activity in conception of innovative functioning of higher educational institutions. The phenomenon «future pre-school teachers’ self-expression culture» is interpreted as peculiarities (different from others personal characteristics), means ( totality of actions used for reaching the aim), results ( intermediate and final products) of self-organized professional activity. In particular, the structural components (cognitive, emotional, and behavioural) are specified on the basis of psychological and pedagogical literature; criteria and indicators of estimation of the formation of the culture of self-expression are singled out; сriteria and indicators of estimation of the formation of the culture of self-expression, which are the characteristics of the personality of future specialists in preschool education, are singled out, corresponding to the main vectors of pedagogical activity (business, acciological, communicative, transformative) and on this basis the typology of the formed phenomenon is determined. The evaluation of effectiveness of developed model of future pre-school teachers’ self-expression culture progress in artistic activity is put into practice by means of the same diagnostic methods which were used during the ascertaining experiment. Attention is paid to received information of the control poll in the experimental group. The analysis of qualitative and quantitative results is realized, the positive dynamics – increase of quantity of future pre-school teachers with spiritual and personal oriented type of self-expression culture in artistic activity is emphasized which let us confirm the effectiveness of the model of this phenomenon’s development proposed by the author. Key words: human-centrism, pedagogical humanism, spirituality, creative self-expression, artistic activity, future educator of establishments of preschool education, quantitative and qualitative analysis of the results in the study; forming and control experiment.